Prospects on Cattle Based Crop-Livestock Systems for The Irrigated Paddy Field in Lombok - Hasil Sembiring; Tanda Panjaitan; Mashur .; Dwi Praptomo; A Muzani; A Sauki; Wildan .; Mansyur .; Sasongko .; Nurul A (Indonesian Center for Animal Research and Development, 2002)
Grouped livestock management is one of the characteristic animals raising in Lombok. In the year of 2000, there were 1096 farmers' group that had a very potential opportunity to optimize the livestock productions through the crop-livestock systems approach. The assessment of this approach for the irrigated paddy field area has being conducted in the village of Sepakok, sub- district of Pringgarata, district of Lombok Tengah. The objective of the study was to improve the efficiency and sustainability of the crop-livestock system as well as environmentally friendly issues. A total of 112 household farmers were involved in the study, joined in the